Civil-military cooperation: an algorithm for effective interaction of public organizations and higher military education institutions - Kuruch , A. (Problems of Engineer-Pedagogical Education, 2023)
The article examines the process of formation of civil-military cooperation in Ukraine. Civil-military cooperation is a function of the armed forces of NATO member states, which is carried out both by military management bodies at the strategic and operational levels, and by military units and units at the tactical level. The functions and tasks of civil-military cooperation are considered. The activity of civil society institutions in Ukraine (public organizations, unions, volunteer movements) is considered. The directions of civil society institutions that exist in Ukraine today and represent the urgent needs of civil society in Ukraine are analyzed. The form of civil-military cooperation of the armed forces in Ukraine is analyzed. The task of civil-military cooperation of the National Guard of Ukraine, in particular cooperation with civil society institutions, is analyzed. A conclusion was made about the need for interaction between public organizations and higher education institutions in order to help future officers develop certain interaction skills. In particular, such an algorithm can be applied in conducting joint events. The article considers the need to involve future officers in sports events, events of national-patriotic education together with institutions of civil society. The need for cooperation between higher military education institutions and civil society institutions, the beneficiaries of which are military veterans, is considered.